A policy mix approach for assessing rural household resilience to climate shocks: Insights from Northeast Brazil. Issue 4 (4th July 2022) - Milhorance, Carolina; Le Coq, Jean-François; Sabourin, Eric; Andrieu, Nadine; Mesquita, Patrícia; Cavalcante, Louise; Nogueira, Daniela
ABSTRACT: Climate change adaptation is a cross-cutting policy issue that accounts for a diversity of policy approaches, tools, and goals. Unclear conceptualization and the absence of comparable metrics are challenges that hinder the assessment of progress toward policy goals. This study draws on a policy mix approach to analyze adaptation efforts at the subnational level. It examines the complex pathways by which rural households in Northeast Brazil build resilience capacities and deal with drought with policy support. Particular emphasis is placed on the implementation of policy mixes composed of climate-related and broader development instruments as well as on the coordination of these instruments in the mix. The resilience of households benefiting from different instrument mixes is examined, and the results show a trend toward an intermediary value for our composite resilience metric highlighting the adoption of coping rather than transformative adaptive strategies. However, changing these trends toward enhanced resilience pathways depends on the improved implementation of the policy mixes and on political factors that include administrative issues, but also coordination and negotiation among policy actors.